Hybrid demodulation method for distributed acoustic sensing based on coherent detection and pulse pair. (31st December 2019) - Chen, Wenjie; Jiang, Junfeng; Wang, Shuang; Liu, Kun; Ma, Zhe; Liang, Guanhua; Ding, Zhenyang; Zhang, Yongning; Niu, Panpan; Liu, Tiegen
Abstract: A hybrid demodulation method based on coherent detection and pulse pair for distributed acoustic sensing is proposed. The Rayleigh backscattering light of pulse pair is coherent amplified by local reference light. A 3 × 3 fiber coupler is utilized to produce stable 2 π /3 phase shift for phase extraction. The digital mixing of the beat signals of two pulses suppress the noise caused by phase drift and vibration on the local reference fiber. Several simulated acoustic waveforms are detected and retrieved. Experimental results show that the system has good linear response. And the equivalent strain of noise is as low as 0.4 n ε .